The Role of Equatorial Oceanic Waves in the Activation of the 2006 Indian Ocean Dipole - Iskhaq Iskandar (Institute for Research and Community Services (LPPM) ITB, 2012)
Observations and a linear wave model were used to evaluate the role of equatorial oceanic wave processes in affecting the evolution of the 2006 positive Indian Ocean Dipole (IOD), focusing on the activation phase of the event. The observations indicate the presence of upwelling equatorial waves and westward near-surface zonal currents along the equator during the activation phase of the event in August 2006. These upwelling equatorial waves (negative sea surface height anomalies) and westward zonal current anomalies contributed to significant sea surface cooling in the eastern equatorial Indian Ocean. The model results reveal that the upwelling equatorial waves and westward nearsurface zonal currents were mainly generated by wind-forced Kelvin waves associated with the easterly wind anomalies. On the other hand, anomalous easterly winds along the equator during June caused downwelling waves (positive sea surface height anomalies) in the off-equatorial region which propagated westward and elevated sea levels in the western region. The model further shows that a complex interplay of wind-forced and boundary-generated Rossby waves elevated sea levels in the western equatorial Indian Ocean during the activations phase of the 2006 IOD event.